Asymmetric Cyanoethoxy Carbonylation Reaction of Aldehydes Catalyzed by a TiIV Macrocyclic Complex: An Efficient Synthetic Protocol for β‐Blocker and α1‐Adrenergic Receptor Agonists. Issue 6 (9th January 2013) - Sadhukhan, Arghya; Choudhary, Manoj K.; Khan, Noor‐ul H.; Kureshy, Rukhsana I.; Abdi, Sayed H. R.; Bajaj, Hari C.
Abstract Chiral macrocyclic TiIV–salen complexes were used as efficient catalysts in the asymmetric cyanoethoxy carbonylation of aldehydes. The TiIV catalysts demonstrated excellent performance (product yields and ee values up to 99 %) with ethyl cyanoformate as the cyanide source and a catalyst loading of 0.5 mol %, which is the lowest known. The macrocyclic TiIV–salen complex retained its performance at multigram level and was conveniently recycled for a number of times. The product obtained was straightforwardly transformed to the pharmaceutically important chiral drugs (R)‐proethalol (β‐blocker) and (R)‐phenylephrine (α1‐adrenergic receptor agonist) in good yields. To understand the mechanism of the catalytic reaction, a kinetic investigation was conducted with various concentrations of the catalyst, ethyl cyanoformate and benzaldehyde as the representative substrate. The reaction of benzaldehyde was first order with respect to the concentration of the catalyst and the ethyl cyanoformate but did not depend on the initial concentration of the substrate. A possible mechanism of the cyano‐ethoxy carbonylation reaction was proposed.